Design for Postplacement Mousing based on GSM in Long-Distance - Xin Gao; Bo Zhang; Shixiong Liang; Dong Xing; Junlong Wang (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
This design for mousing is made up of power control module, infrared sensor module, signal processing module, distance information transportation based on GSM and device of power grid. The design consists of two sets of conductors, separately linked by fire wire and null line and distributing alternatively. The major innovation is infrared sensor module with Fresnel lens, and that the infrared detecting area should be spread in one direction at least. When the mouse get into the infrared detecting area, the sensor signal of infrared detecting device is sent to power control module through signal element and then starts the device of power grid to power up to make the mouse be shocked or die. GSM module is adopted to tell that the mouse is caught successfully. This design can be placed in any position that the mouse is always out and no need of baits.